Resurgence of pertussis calls for re-evaluation of pertussis animal models. (September 2012) - van der Ark, Arno AJ; Hozbor, Daniela F; Boog, Claire JP; Metz, Bernard; van den Dobbelsteen, Germie PJM; van Els, Cécile ACM
Pertussis has recently re-emerged in well-vaccinated populations most likely due to a combination of pathogen adaptation and waning of vaccine-induced pertussis immunity. Changes in genomic content of the etiologic agent, Bordetella pertussis, observed in the postvaccination era can have a bearing on the efficacy of vaccines currently in use. Moreover, protective immune responses in vaccinees wane gradually depending on their originally induced size and breadth, and memory responses may not be as regularly boosted by circulating strains as was the case in the prevaccination era. This pertussis scenario asks for new, improved vaccines with at least a longer duration of protection. Pertussis vaccine research, development and postmarketing surveillance require re-evaluation and innovation of the currently available pertussis animal models, with emphasis on the use of circulating B. pertussis strains.